Orthopaedic registries – the UK view (National Joint Registry): impact on practice. Issue 6 (June 2019) - Porter, Martyn; Armstrong, Richard; Howard, Peter; Porteous, Matthew; Wilkinson, J. Mark
Abstract : The National Joint Registry (NJR) was established in 2002 as the result of an unexpectedly high failure rate of a cemented total hip replacement. Initial compliance with the Registry was low until data entry was mandated. Current case ascertainment is approximately 95% for primary procedures and 90% for revision procedures. The NJR links to other data sources to enrich the reporting processes. The NJR provides several web-based and open-access reports to the public and detailed confidential performance reports to individual surgeons, hospitals and industry bodies. A transparency and accountability process ensures that device and surgical performance are actively monitored on a six-monthly basis, and adverse variation is dealt with in an appropriate way that underpins patient safety. The NJR also manages a comprehensive research-ready database and data protection compliant access system that enables external researchers to use the dataset and perform independent analyses for patient benefit. Moving forwards, the NJR intends to look at factors that lead to better outcomes so that good practice can be embedded into routine care. Cite this article: EFORT Open Rev 2019;4 DOI: 10.1302/2058-5241.4.180084